FACTORS THAT AFFECT THE INCIDENT OF LOW BIRTH WEIGHT(LBW) IN REGIONAL GENERAL HOSPITAL OF ARIFIN ACHMAD, PEKANBARU (JURNAL IBU DAN ANAK, 2020)
Abstract Low birth weight (LBW) is closely related to infant mortality and morbidity.The LBW would be at risk of still birth, growth and development retardation.Besides that, individuals with a history of LBW have a high risk factor for theincidents of hypertension, heart disease and diabetes after reaching the ageof 40 years (Kosim MS in Mahayana, 2012).The purpose of this study is to determine the factors that influence the incidentof LBW in Regional General Hospital of Arifin Achmad, Pekanbaru 2018.This research was an analytic using a cross-sectional research design,. Thedata were taken from medical record. The population in this study were all ofmaternal women whose babies were treated in the perinatology room ofRegional General Hospital of Arifin Achmad, Pekanbaru. The total ofpopulation and sample are 328 and 250 respectively.The results show that: there is no significant relationship between maternal ageand LBW incident 0.990 (p-value> 0.05), no correlation between parity and LBW incident with p value = 0.661 (p value>α), there is no significantrelationship between the illness of mother during pregnancy with LBW incident with p value = 0.773 (p value>α), no significant relationship betweenplacental abnormalities during pregnancy and incident of LBW with p value = 0.153 (p value>α) , there is a significant relationship between pregnancy ageand LBW incident with p value = 0.000 (p value ≤ α), and there is a significant relationship between twin pregnancy and incident of LBW with pvalue = 0.002 (p value>α). From this research, it can be suggested that the community, especiallypregnant women and their families to increase much more information onmaternal and child health through social media, to attend counseling andseminars, and to ask the medical personnels directly to the nearest healthfacilities about LBW. By these suggestions LBW hopefully could be avoided.Keyword : Low Birth Weight (LBW)